'Sweeter' than its name: anti-inflammatory activities of Stevia rebaudiana. Issue 1 (1st January 2020) - Zou, Xiaomin; Tan, QiWen; Goh, Bey-Hing; Lee, Learn-Han; Tan, Kai-Leng; Ser, Hooi-Leng
ABSTRACT: Inflammation plays a major role in etiology of multiple diseases and it has become an imperative therapeutic target in pharmacological interventions. Over the years, natural products originating from plants have made great contributions in the drug discovery process. Belonging to the Asteraceae family, Stevia rebaudiana ( S. rebaudiana ) is exploited at a large scale for its purpose as a natural sweetener. Even so, researchers have begun to notice other bioactive potential use of stevia such as anti-inflammatory and anti-cancer activities, which are conferred by compounds present in the leaves including stevioside, rebaudioside and isosteviol. In this review, we provide a brief overview of S . rebaudiana plant and its bioactive compounds and highlight their anti-inflammatory potential for therapeutic applications.